Inventory reporting of livestock emissions: the impact of the IPCC 1996 and 2006 Guidelines - Amon, Barbara; Çinar, Gültaç; Anderl, Michael; Dragoni, Federico; Kleinberger-Pierer, Magdalena; Hörtenhuber, Stefan (Environmental research letters, 2021)
The livestock sector is a major contributor to agricultural greenhouse gas (GHG) and nitrogen (N) emissions and efforts are being made to reduce these emissions. National emission inventories are the main tool for reporting emissions. They have to be consistent, comparable, complete, accurate and transparent. The quality of emission inventories is affected by the reporting methodology, emission factors and knowledge of individual sources. In this paper, we investigate the effects of moving from the 1996 IPCC Guidelines for National Greenhouse Gas Inventories to the 2006 IPCC Guidelines on the emission estimates from the livestock sector. With Austria as a case study, we estimated the emissions according to the two guidelines, revealing marked changes in emission estimates from different source categories resulting from changes in the applied methodology. Overall estimated GHG emissions from the livestock sector decreased when applying the IPCC 2006 methodology, except for emissions from enteric fermentation. Our study revealed shifts in the relative importance of main emission sources. While the share of CH 4 emissions from enteric fermentation and manure management increased, the share of N 2 O emissions from manure management and soils decreased. The most marked decrease was observed for the share of indirect N 2 O emissions. Our study reveals a strong relationship between the emission inventory methodology and mitigation options as mitigation measures will only be effective for meeting emission reduction targets if their effectiveness can be demonstrated in the national emission inventories. We include an outlook on the 2019 IPCC Refinement and its potential effects on livestock emissions estimates. Emission inventory reports are a potent tool to show the effect of mitigation measures and the methodology prescribed in inventory guidelines will have a distinct effect on the selection of mitigation measures.